In vivo confocal microscopy of climatic droplet keratopathy. (19th March 2013) - Bhikoo, Riyaz; Niederer, Rachael L; Hart, Richard; Sherwin, Trevor; McGhee, Charles NJ
<x xml:space="preserve">Abstract</x> We describe the corneal microstructural changes in a patient with spheroidal degeneration using in vivo confocal microscopy. Multiple hypo‐ and hyper‐reflective spherical lesions were observed in the anterior corneal stroma and Bowman's layer ranging from 45 to 220 μm in size. The corneal epithelium, posterior stroma and endothelium were otherwise unaffected. In vivo confocal microscopy demonstrates good correlation with excised histological samples in climatic droplet keratopathy. It provides a non‐invasive technique to examine the living cornea for degenerative disease and acts as a bridge between clinical and laboratory observations.